SHIFTING MEANING OF SACREDNESS IN RELIGIOUS RITUALS SOCIOLOGICAL STUDIES OF INDIGENOUS PEOPLES IN THE ERA OF MODERNIZATION - Ismail, Muhammad (Jurnal Asy-Syukriyyah, 2025)
This study examines the transformation of religious rituals in indigenous communities during the era of modernization. The study highlights three main aspects: the shift in sacred meaning, syncretism between Islamic values and local traditions, and the role of indigenous and religious institutions in responding to modernization. Technology allows for broader participation through digital media, but raises questions about the importance of physical presence. Globalization transforms rituals into global attractions, while commodification shifts the focus from sacredness to economic aspects. Despite these changes, some indigenous communities continue to uphold their ancestral traditions. The integration of Islamic values with local traditions demonstrates that modernization can be harmonized without eliminating sacredness. Syncretism between Islam and local traditions reflects cultural adaptation without losing identity. Indigenous and religious institutions play a crucial role in preserving customs, maintaining social norms, resolving disputes, and collaborating with village governments. Regulatory support and policies are needed to ensure cultural preservation and protect indigenous communities' interests.